Proceso de atención de enfermería en seguridad y prevención de eventos que afectan la salud del paciente con infección de herida quirúrgica post cesárea en el Hospital de Guasmo Sur - Becilla Tomala, Geomayra Mabel (2020)
The present clinical case aims to establish the nursing care process in preventing events that affect the health of the patient with post-cesarean surgical wound infection in the south guasmo hospital. Therefore, the descritive method is used by means of the investigación carried out, the types of surgical wounds and the factors that influence this contamination are disclosed. This case study reveals the importance of the care plan in a patient with a surgical wound that presents purulent secretions. For this, a plan was developed to evaluate, in accordance whit the theories that resembles my clinical case, which will lead to a good nursing diagnosis.